2015
DOI: 10.1124/dmd.115.064246
|View full text |Cite
|
Sign up to set email alerts
|

Indole and Tryptophan Metabolism: Endogenous and Dietary Routes to Ah Receptor Activation

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor recognized for its role in xenobiotic metabolism. The physiologic function of AHR has expanded to include roles in immune regulation, organogenesis, mucosal barrier function, and the cell cycle. These functions are likely dependent upon ligandmediated activation of the receptor. High-affinity ligands of AHR have been classically defined as xenobiotics, such as polychlorinated biphenyls and dioxins. Identification of endogenous AHR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
432
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(452 citation statements)
references
References 142 publications
6
432
0
Order By: Relevance
“…Results from a variety of laboratories over the past decade have revealed that the AHR has key roles in the development of cardiovascular, reproductive, and neural systems as well as in hematopoiesis and regulation of immune responses (Benedict, Lin, Loeffler, Peterson, & Flaws, 2000; Esser & Rannug, 2015; Gasiewicz, Singh, & Bennett, 2014; Kimura, Ding, & Tohyama, 2016; Lahvis et al., 2005; Quintana & Sherr, 2013; Singh et al., 2014; Stockinger, Di Meglio, Gialitakis, & Duarte, 2014). Some of these functions may involve natural or endogenous ligands such as metabolites generated by the microbiome, tryptophan metabolites, or lipid‐derived molecules (Bessede et al., 2014; Hubbard, Murray, & Perdew, 2015; McMillan & Bradfield, 2007; Moura‐Alves et al., 2014). The exact relationship between the AHR‐dependent toxicity of DLCs and PAHs and these physiological roles of AHR is not yet clear.…”
Section: Ahr Pathwaymentioning
confidence: 99%
“…Results from a variety of laboratories over the past decade have revealed that the AHR has key roles in the development of cardiovascular, reproductive, and neural systems as well as in hematopoiesis and regulation of immune responses (Benedict, Lin, Loeffler, Peterson, & Flaws, 2000; Esser & Rannug, 2015; Gasiewicz, Singh, & Bennett, 2014; Kimura, Ding, & Tohyama, 2016; Lahvis et al., 2005; Quintana & Sherr, 2013; Singh et al., 2014; Stockinger, Di Meglio, Gialitakis, & Duarte, 2014). Some of these functions may involve natural or endogenous ligands such as metabolites generated by the microbiome, tryptophan metabolites, or lipid‐derived molecules (Bessede et al., 2014; Hubbard, Murray, & Perdew, 2015; McMillan & Bradfield, 2007; Moura‐Alves et al., 2014). The exact relationship between the AHR‐dependent toxicity of DLCs and PAHs and these physiological roles of AHR is not yet clear.…”
Section: Ahr Pathwaymentioning
confidence: 99%
“…The ability of the AHR also to regulate immune function and intestinal homeostasis in a manner that appears to involve microbiota-generated metabolites is currently of high interest. With this in mind, Hubbard et al (2015) focused on our emerging understanding of the metabolic formation of endogenous AHR ligands from tryptophan and indole by both the host and gut microbiota. In addition, they speculated on how the absence or presence of these metabolites may impact gut homeostasis, barrier function, and the gut inflammatory response via their AHR modulating activities.…”
Section: Contribution Of the Gut Microbiota To Intestinal Immune Homementioning
confidence: 99%
“…A variety of tryptophan metabolites (e.g., indole, indole-3-aldehyde, indole-3-acetic acid, and indole-3-propionic acid) are generated primarily by bacterial metabolism in the colon and are then absorbed and circulated systemically [59, 60]; thus, plasma levels of these bacterial products are substantially lower in germ-free mice compared to conventional mice [61]. The nuclear receptors AhR (aryl hydrocarbon receptor) and PXR (pregnane/xenobiotic responsive receptor or pregnane X receptor) are molecular targets of these bacteria-derived tryptophan metabolites [59, 60, 62].…”
Section: Tryptophan Metabolitesmentioning
confidence: 99%